Dark triad psychopathy outperforms self-control in predicting antisocial outcomes: a structural equation modeling approachseabream - Pechorro, Pedro (2022)
Dark Triad traits and self-control are considered viable causal precursors to antisocial and criminal outcomes in youth. The purpose of the present study is to concurrently compare how Dark Triad traits and self-control differ in terms of predicting self-reported juvenile delinquency, CD symptoms, proactive overt aggression, and crime seriousness. The sample consisted of 567 (M = 15.91 years, SD = 0.99 years, age range = 14–18 years) Southern European youth from Portugal. Structural-equation-modelling procedures revealed that the psychopathy factor of Dark Triad traits presented the strongest significant hypothetical causal associations with the antisocial/criminal outcomes, followed by self-control. Machiavellianism and narcissism presented the lowest causal associations. Our findings indicate that psychopathy, as operationalized in the Dark Triad, concurrently surpasses self-control and the remaining factors of the Dark Triad in terms of predicting antisocial/criminal outcomes in youth. This suggests that behavioral disinhibition, or a core incapacity to regulate one’s conduct, is central for understanding delinquency and externalizing psychopathology. Comparatively, the interpersonal component of dark personality features, such as Machiavellianism and narcissism, are secondary for understanding crime.